طريقة زرّ المتكلم لترقية مهارة الكلام - Aliwafa; Thohir, Muhammad; Khotimah, Khusnul; Kamilah, Amaliyatul (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Maharah kalam is one of the anger or skills in learning Arabic that requires students to be active in speaking. In practice, many students have difficulty communicating using Arabic. This happens because they do not understand and do not even have the courage to pronounce sentences in Arabic for fear of being wrong and so on. So the researcher wants to apply the talking chips type of cooperative learning model to facilitate and assist students in learning to speak Arabic and build the mentality of students to dare to speak Arabic. The results of this study indicate the success of using the talking chips type of cooperative learning model.